(untitled) (Research, Society and Development, 2022)
The present study aimed to analyze the rates of vaccination coverage and the rate of abandonment of the Polio vaccination schedule in Brazil and Minas Gerais between 2018 and 2021, in order to evaluate the influences of the pandemic on these parameters of immunization against Polio. This is a descriptive and retrospective study on Polio vaccination coverage between the years 2018 and 2019 (pre-pandemic) and during the pandemic, the years 2020 and 2021 in Brazil and Minas Gerais. Data were obtained from the National Immunization Program Information System. In temporal analysis, two clippings are demonstrated: pre-pandemic and pandemic, with different results, as expected. Despite the concordance between national and Minas Gerais parameters, it is important to analyze regional particularities. The study by Franco et al. (2020), who correlated Polio vaccination coverage in Brazil and sociodemographic variables, identified that the regions of the country that did not reach adequate coverage were those with the highest Human Development Index, higher education and greater access to the internet. Furthermore, no direct relationship was observed between health care and the vaccination coverage rate. Thus, the present study identified the low rate of vaccination coverage in Brazil and Minas Gerais in the pandemic period in relation to the pre-pandemic scenario. On the other hand, the dropout rate over the years 2018 to 2021 showed alternations, demonstrating less evasion of the Polio vaccine schedule in the pandemic compared to the year 2019.